2022
DOI: 10.3389/fgene.2022.810292
|View full text |Cite
|
Sign up to set email alerts
|

Identification of GGT5 as a Novel Prognostic Biomarker for Gastric Cancer and its Correlation With Immune Cell Infiltration

Abstract: Gastric cancer (GC) is a common malignant tumor of the digestive system. Recent studies revealed that high gamma-glutamyl-transferase 5 (GGT5) expression was associated with a poor prognosis of gastric cancer patients. In the present study, we aimed to confirm the expression and prognostic value of GGT5 and its correlation with immune cell infiltration in gastric cancer. First, we compared the differential expression of GGT5 between gastric cancer tissues and normal gastric mucosa in the cancer genome atlas (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…GGT5, the protein with the strongest correlation with the BEP score, is highly expressed in macrophages and its tissue expression correlates with macrophage infiltration. 52 Cluster of differentiation 14 (CD14), an important macrophage surface marker, is also elevated in MC2 endplate‐near bone marrow. Therefore, our data point at increased numbers of macrophages in MC2.…”
Section: Discussionmentioning
confidence: 99%
“…GGT5, the protein with the strongest correlation with the BEP score, is highly expressed in macrophages and its tissue expression correlates with macrophage infiltration. 52 Cluster of differentiation 14 (CD14), an important macrophage surface marker, is also elevated in MC2 endplate‐near bone marrow. Therefore, our data point at increased numbers of macrophages in MC2.…”
Section: Discussionmentioning
confidence: 99%
“…GGT5 (Gamma-Glutamyltransferase 5) is a member of the gamma-glutamyl transpeptidase gene family involved in glutathione metabolism ( Wickham et al, 2011 ). GGT5 was associated with immune cell infiltration and might be a potential immunological therapeutic target in gastric cancer ( Wang et al, 2022 ). ASAH1 (N-Acylsphingosine Amidohydrolase 1) encodes a member of the acid ceramidase family of proteins and is involved in glycosphingolipid metabolism ( Li et al, 1999 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have found that different types of immune cells infiltrate tumors in large numbers and that their distribution, tissue location, and cell type are all linked to tumor development and survival ( 17 ). We found that the expression levels of FCN2 are abnormally low in HCC.…”
Section: Discussionmentioning
confidence: 99%